If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -4y = -28 Solving 5x + -4y = -28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. 5x + -4y + 4y = -28 + 4y Combine like terms: -4y + 4y = 0 5x + 0 = -28 + 4y 5x = -28 + 4y Divide each side by '5'. x = -5.6 + 0.8y Simplifying x = -5.6 + 0.8y
| 5x+23=10x-67 | | 5x+23=10x-68 | | 75-3x=10x-4x | | z^4-8z^2+15=0 | | 6x+12.3-10.2=1.5 | | Z-y-b= | | -p-1=-21 | | (K-p)*(r-j)= | | 3x^2-6x=x^2+x | | z+4=-4 | | m-8=-5 | | z+6=-6 | | z-7=3 | | z-7=0 | | 12+y=0 | | h/40=5 | | y-1.2=-1.3 | | 4x-3=x-15 | | a-5=66 | | x^2-6x+1=2-6x | | 5x-6=1-6x | | 7x-6=1-5x | | 6x^2+20x+12=0 | | x^2-5x+4=19-3x | | 4x+8-x+3=2x+23 | | y^2+3y+yx+3x=0 | | 10x-37=-87 | | x=8-3x | | (x-8)=4 | | (X*0.1)+X=100 | | (100*0.1)+100=X | | X*0.1=100 |